Pengembangan Profesionalisme Guru dalam Pendidikan Anak Usia Dini di RA Al-Hidayah - Mutia Muhalisiah; Astuti Darmiyanti; Nidaul Muna'fiah (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
The development of early childhood education institutions in Indonesia is currently experiencing rapid progress. This increase can occur if there are many young children who need care (AUD). Quality is also directly proportional to the need for qualified teachers. The demand to become a quality educator reclaims early childhood development, the golden age of quality teachers who can influence the next generation of superior Indonesians, the cornerstone of early childhood excellence. Many initiatives suggest improvement by improving the quality of early childhood educators so that the quality of early childhood education services can be improved. This study is intended to find out how the outstanding skills of instructors at RA AL-HIDAYAH improve. In addition, this research was conducted at RA AL-HIDAYAH. Based on research findings on the professional development of a teacher, a term that can refer to a mental attitude in the form of a commitment from members of a profession to always realize and improve the quality of their profession, the respondents include the head of Ra Al -School Hidayah and all teachers. The research method used is qualitative with descriptive research techniques. The teaching profession is one that assumes an important part in the country's daily routine. The quality of education is greatly influenced by how well teachers carry out their responsibilities, because the education system is influenced by teachers and society. Therefore, the advancement of the teaching profession is an absolute requirement for the progress of the nation. The quality of educational processes and outcomes will also improve as a result of better educators. The progress of the impressive skills of educators in RA AL-HIDAYAH is very much reflected in the calling of an educator, but leaders for this situation should also continue to strive to live up to the educator's calling by involving them more regularly through various school programs and the preparation of both is coordinated by the Training Office in Kab. the Karawang.